Environmentally sustainable elimination of microbes using boron-doped diamond electrodes: From water treatment to medical applications - Koch, Maximilian; Rosiwal, Stefan; Burkovski, Andreas (Microbial Biotechnology: Role in Ecological Sustainability and Research, 2022)
Boron-doped diamond electrodes can be applied in a so-called advanced oxidation process to generate different reactive oxygen species (ROS) in water. These ROS may react with any carbon-containing molecule, which is present in the solution, and form carbon monoxide and carbon dioxide as endproducts of the oxidation process. This mechanism can be exploited for different disinfection processes. In recent years, boron-doped diamond electrodes were applied successfully for the inactivation of microorganisms. Examples presented here are proof-of-principle studies related to cleaning of potable water, wastewater treatment, and applications in dentistry.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Antibiotic resistance; BDD; Biofilm; Boron-doped diamond; Disinfectants; Implants; Oxygen radicals; Peri-implantitis; Root canal treatment